A Joint Radar and Communication Approach Based on Phase-Coded FMCW Chirp Sequences - Alami El Dine, Mohamad; Stelzig, Michael; Schür, Jan; Vossiek, Martin (International Conference on Microwaves for Intelligent Mobility (ICMIM), 2024)
Joint radar and communication (RadCom) systems are an emerging solution to the spectrum congestion problem that has attracted the attention of both scientific and industrial researchers—for example, in the field of autonomous systems. In this contribution, we propose a novel signaling approach utilizing a chirp sequence radar to seamlessly integrate communication capabilities into the system. The concept relies on a correlation-based synchronization and can estimate and compensate phase errors caused by Doppler frequency shifts in the received signals. Measurement results at 25-GHz confirmed the system’s simulated performance.<br
CRIS-Team Scopus Importer:2024-09-06
Keywords: Chirp sequence; PC-FMCW; RadCom.